Numerical simulation of the wind influence on bottom shear stress and salinity fields in areas of Zostera noltei replanting in a Mediterranean coastal lagoon. (April 2018) - Alekseenko, E.; Roux, B.
Highlights: Process of haline stratification in lagoon for a large freshwater runoff. Process of haline destratification in lagoon generated by a strong wind. Velocity and salinity distribution in the Caronte channel. Specific effect of downwind coastal jets on the bottom shear stress. Use of bottom shear stress map to select relevant sites for SAV replanting. Abstract: The paper concerns the numerical simulation of the wind influence on bottom shear stress and salinity fields in a semi-enclosed coastal lagoon (Etang de Berre) which is connected to the Mediterranean through a long and narrow channel (called Caronte). Two different scenarios are considered. The first scenario (scen.#1), starting with a homogeneous salinity of S = 20 PSU and without wind forcing, studies a stratification process under the influence of a periodic seawater inflow and a strong freshwater inflow from a hydropower plant (250 m 3 /s). Then, in the second scenario (scen.#2), we study how a strong wind of 80 km/h can destroy the haline stratification obtained at the end of scen.#1. The MARS3D numerical model is used to analyze the 3D current and salinity distribution induced by these three meteorological, oceanic and anthropogenic forcings in this lagoon and in the Caronte channel. The main goal is to determine the bottom shear stress (BSS) in the nearshore areas of Zostera noltei replanting, and to compare it with the threshold for erosion of the bottom sediments for different bottom roughness parameters. The most interesting results concern the four nearshore replanting areas; two are situated on the eastern side of EB and two on the western side. The results of scen.#2 show that all these areas are subject to a downwind coastal jet. The destratification process is very beneficial; salinity always remains greater than 12 PSU for a N-NW wind of 80 km/h and a hydropower runoff of 250 m 3 /s. Concerning BSS, it presents a maximum near the shoreline and decreases along transects perpendicular to the shoreline. There exists a zone, parallel to the shoreline, where BSS presents a minimum (where BSS = 0). When comparing the BSS value at the four control points with the critical value, BSS cr, at which the sediment mobility would occur, we see that for the smaller bottom roughness values (ranging from z 0 = 3.5 × 10 −4 mm, to 3.5 × 10 −2 mm) BSS largely surpasses this critical value. For a N-NW wind speed of 40 km/h (which is blowing for around 100 days per year), BSS still largely surpasses BSS cr - at least for the silt sediments (ranging from z 0 = 3.5 × 10 −4 mm, to 3.5 × 10 −3 mm). This confirms the possibility that the coastal jet could be a stressor for SAV replanting.